Inkjet-Printed Conductive Patterns on Electrospun Substrates for the Modular Fabrication of Nonplanar Circuits - Molinari, Fabricio Nicolás (2025)
Placing printed conductive patterns onto nonplanar substrates is a challenging task. In this work, we tested a simple method for depositing inkjet-printed conductive patterns onto 3D-printed pieces with cavities and sharp edges. First, a silver nanoparticle ink was used to print conductive patterns onto a flexible and porous substrate made of electrospun polycaprolactone (PCL). Then, the printed patterns were transferred to 3D-printed pieces made of polylactic acid (PLA) by temperature-promoted adhesion. Finally, the printed patterns were cured to render them conductive. The influence of the number of printed layers on their electrical and mechanical properties was evaluated. The printed patterns were also transferred to flexible substrates, such as thermoplastic polyurethane (TPU) and polyethylene terephthalate (PET) sheets, achieving conductivity after curing. Moreover, the printed patterns were effective for modular interconnection among successive transferred patterns, since it was possible to achieve electrical contact between them during the transfer process.